THE INFLUENCE OF FINANCIAL LITERACY, FAMILY ENVIRONMENT, LOVE OF MONEY, AND SELF-EFFICACY ON ENTREPRENEURIAL INTEREST AMONG ACCOUNTING STUDENTS AT POLITEKNIK NEGERI SAMARINDA - Rama Yuni, Rama Yuni; Ahyar, Muhammad Khozin Ahyar; Nyoria, Nyoria Anggraeni Mersa (Journal of Management and Islamic Finance, 2024)
This research aims to determine the influence of financial literacy, family environment, love of money and self-efficacy on students' interest in entrepreneurship at the Accounting Department, Politeknik Negeri Samarinda. The aim of this research is to determine the influence of financial literacy, family environment, love of money and self-efficacy on students' interest in entrepreneurship at the Accounting Department, Politeknik Negeri Samarinda. The population of this study was 861 students. Meanwhile, the sample in this research was 300 students. The data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis. The research results show that financial literacy has no effect and is not significant on interest in entrepreneurship. Family environment has a positive and significant effect on interest in entrepreneurship. Love of money has a positive and significant effect on interest in entrepreneurship. Self-efficacy has a positive and significant effect on interest in entrepreneurship. The results of this study indicate that there needs to be more encouragement for accounting students department at Politeknik Negeri Samarinda to be able to build an entrepreneurial spirit.